2016
DOI: 10.1097/bot.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Patients With Type 3 Open Fractures: Comparing Antibiotic Prophylaxis With Cefazolin Plus Gentamicin Versus Piperacillin/Tazobactam

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Redfern et al. compared a combination of cefazolin and gentamicin with piperacillin/tazobactam in G–A type III fractures [ 26 ]. They reported that there was no significant difference between treatments and the rate of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redfern et al. compared a combination of cefazolin and gentamicin with piperacillin/tazobactam in G–A type III fractures [ 26 ]. They reported that there was no significant difference between treatments and the rate of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we could not evaluate contamination of the wound quantitatively. Previous studies have reported that a contaminated wound increases the deep infection rate [ 25 , 26 , 33 ]. Nevertheless, there are no standard criteria for determining whether a wound is severely contaminated with mud, sand, or seawater; therefore, additional experimentation is needed in the future to evaluate these criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Rupp et al advocated the use of additional gram-negative antibiotic coverage for Gustilo-Anderson type III fractures and high dose penicillin prophylaxis if faecal or clostridia contamination is suspected [10]. However, prophylaxis with piperacillin/tazobactam showed no inferior results compared to the combined use of cephalosporin and gentamicin for Gustilo-Anderson type III open fractures with regard to surgical site infections after 30 days, fracture non-union, re-hospitalization rates or deaths at one year [11].…”
Section: Discussionmentioning
confidence: 99%
“…24, 36 With the aim of avoiding some of the complications of aminoglycocides, more recent studies have explored the use of alternative gram-negative coverage. Ceftriaxone 38 , piperacillin/tazobactam 39 , cefotaxime 40 , and cefepime 41 have all been investigated and been found to be either superior or no less effective. The addition of penicillin for fecal or potential clostridial contamination is also recommended.…”
Section: Subsequent Debridements and Medical Managementmentioning
confidence: 99%